Navigating The Storm: ASEAN's Strategy Amidst Two Major Powers - Sekar Ayu, Galuh Anissa (Global Political Studies Journal, 2023)
This study aims to analyze ASEAN's stance and approach, particularly in managing confrontational politics amidst major power competition, this article will also demonstrate ASEAN's attitudes and policies in navigating confrontational politics, including how ASEAN leverages its regional community norms to respond to such competition. Through this exploration, the author seeks to delve into the role and theoretical implications of ASEAN as a regional actor grappling with the management of political competition in the rapidly evolving East Asian and Indo-Pacific regionalism. The author used an impartial enmeshment concept and a descriptive qualitative method. The results showed that the intense geostrategic competition between China and the United States has placed ASEAN in a dilemma. ASEAN strives to maintain its centrality in the region by fostering fair, impartial, and neutral cooperation relationships. ASEAN bases its approach on the norms and principles of the organization, such as transparency, openness, inclusivity, good conflict management, and the importance of sovereignty and non-intervention (ASEAN Way). The ASEAN Outlook on the Indo-Pacific (AOIP) is one policy that reflects ASEAN's efforts to build a new framework of cooperation based on its own rule in the region. However, this Southeast Asia organization faces several challenges that can threaten its position. Keywords— ASEAN, Indo-Pacific, Impartial, Enmeshment, Geostrategies